Morphology and Interface Engineering for Organic Metal Halide Perovskite–Based Photovoltaic Cells. Issue 14 (10th May 2018) - Wei, Qi; Bi, Huan; Yan, Su; Wang, Shiwei
Abstract: Organic–inorganic metal halide perovskite (OMHP) has become one of the most important optoelectronic materials due to its electronic transport properties and excellent machinability. The efficiency of OMHP solar cells has risen rapidly from 3.81% to more than 20% in the past seven years, which has almost approached the theoretical value. Despite the continuous and in‐depth researches by scientists, it has been difficult to prepare new materials for OMHP devices with high performances. According to literature reported, OMHP solar cells can get remarkable performances depending on not only the mesoscopic structure but also the planar structure. Besides that, the morphology of OMHP film has been considered as the most important impact for high device performances. And the film morphology of OMHP can be affected by many factors including deposition method, material components, additives, post‐treatment process, and so on. The corresponding researches and reports appear constantly, which will be summarized and discussed in detail in this review. It can be concluded that the continuous, uniform growth and dense perovskite crystals in the OMHP film are the key factors for the preparation of high performance OMHP devices. Abstract : With the development of organic metal halide perovskite materials and devices, several methods are investigated to control the film morphology because of the important impact on the photovoltaic device performances, so that the study of perovskite is more abundant. The corresponding main progress in recent two years and outlooks are summarized in this review.